(untitled) (Research, Society and Development, 2022)
Objective: To investigate the cognitive benefits of Music-Based Interventions - MBI for elderly people with Alzheimer’s Disease - AD from a Systematic Review. Method: Publications from the Virtual Health Library and PubMed were collected based on the guiding question: "Does MBI have a positive impact on the cognitive dysfunction of elderly people with AD compared to other non-pharmacological treatments?". The following eligibility criteria were considered: free and full access to the databases; publication between 01/01/2011 and 12/31/2021; language English, Spanish or Portuguese; exclusive selection of Clinical Trials; score above 80% on the Downs and Black scale (1998). Finally, the duplicates were discarded. The final selection included 6 articles, from which the following data were extracted: intended objectives; MBI used; main results achieved; authorship and sampling of publications; duration of interventions; cognitive dysfunction assessment instruments; Downs and Black scale score (1998). Results: 50% of the studies listed as their primary objective the performance of some form of assessment of the cognitive status of their participants. In turn, Memory and Attention were the Cognitive Functions prioritized in the data collection and analysis employed by the researchers, with positive results for the use of MBI. Conclusion: MBI promotes significant benefits for elderly people with AD, both in cognitive terms and in an expanded way, contributing to the production of treatments focused on well-being and quality of life.